Google Sites Sebagai Alternatif Learning Management System (LMS) Dalam Ekosistem Pembelajaran Digital: Tinjauan Literatur Sistematis - Ravsanjani Ravsanjani; Jasrial Jasrial; Abna Hidayati; Septriyan Anugrah; Anggi Prasetia (LPPM Institut Pendidikan Nusantara Global, 2026)
The digital infrastructure gap remains a major challenge in achieving equitable education quality. This study aims to conduct an in-depth literature synthesis on the effectiveness of using Google Sites as a robust alternative Learning Management System (LMS) across various educational ecosystems. Using the Systematic Literature Review (SLR) method and the PRISMA protocol, this study selected 20 journal articles published between 2021 and 2026. The synthesis results indicate that Google Sites has a very high level of validity (averaging above 90%) as an interactive learning medium. Empirically, this platform has been proven effective in improving cognitive understanding (average N-Gain score of 0.74), facilitating collaboration, and boosting student motivation and learning independence by over 80%. Crucial findings from this review confirm that Google Sites' cloud-based nature, zero server costs, and integration with Google Workspace make it the most rational and inclusive LMS solution, especially for schools in low-resource environments. The study concluded that, despite network connectivity challenges, Google Sites is poised to facilitate ongoing digital transformation, including the adoption of artificial intelligence (AI) and inclusive education.